135k views
2 votes
D(-3+x)=kx+9 solve for x

User Kingsb
by
5.1k points

1 Answer

4 votes

d(-3 + x) = kx + 9

  • Distribute d inside the parentheses.

-3d + dx = kx + 9

  • Subtract kx from both sides.

-3d + dx - kx = 9

  • Add 3d to both sides.

dx - kx = 9 + 3d

  • Factor x out of dx - kx.

x(d - k) = 9 + 3d

  • Divide both sides by d - k.

x =
(9+3d)/(d-k)

  • If you want to simplify this even more, factor 3 out of the numerator.

x =
(3(d + 3))/(d-k)

User Janac Meena
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.